Effects of bolt pre-loading variations on performance of GDL in a bolted PEMFC by 3-D FEM analysis. (15th October 2016) - Chien, Chi-Hui; Hu, Yao-Lun; Su, Ting-Hsuan; Liu, Hsuan-Ting; Wang, Chung-Ting; Yang, Ping-Feng; Lu, Ying-Xu
Abstract: This study numerically investigated the effects of different bolt pre-loadings on the performance of the gas diffusion layer (GDL) in a bolted proton exchange membrane fuel cell (PEMFC). Firstly, a complete three-dimensional finite element model of a PEMFC bolted by 12 bolts with a reactive area of 5 cm by 5 cm was established using the commercial software SolidWorks. Then, a pre-loading of 1 MPa to 7 MPa on each bolt was applied, increasing in increments 1 MPa, and the corresponding deformation and stress fields of each component of the fuel cell were obtained using the commercial software ANSYS 15.0/Workbench. Finally, the effects of the bolt pre-loading variations on the performance of the GDL were discussed. The results showed that the compression ratio of the GDL increased linearly with the magnitude of bolt pre-loading, and improving the performance of the GDL. However, when the pre-loading on each bolt reached 7 MPa, the compression ratio exceeded 15%, degrading the efficiency of the PEMFC. Also, by comparing the relationships between bolt pre-loading and conductivity and porosity of GDL, in order to obtain the maximum performance of GDL, an optimum value of 4 MPa for bolt preloading was recommended. Highlights: Effect of bolt pre-loading on deformations is more serious than that of thermal loading. Bolt pre-loading improves compression ratio of GDL. For obtaining a maximum performance of GDL, 4 MPa of bolt pre-loading was recommended. Flow channel volume reduced by bolt pre-loading degrades the efficiency of PEMFC.